2008
DOI: 10.1373/clinchem.2008.115410
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Mass Spectrometry for the Direct Assay of Lysosomal Enzymes in Dried Blood Spots: Application to Screening Newborns for Mucopolysaccharidosis I

Abstract: BACKGROUND:Treatments now available for mucopolysaccharidosis I require early detection for optimum therapy. Therefore, we have developed an assay appropriate for newborn screening of the activity of the relevant enzyme, ␣-L-iduronidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 8 publications
3
94
0
2
Order By: Relevance
“…The advantage of using DBS for enzymatic diagnosis of MPS and ML II/III has been demonstrated (Chamoles et al 2001b;Chamoles et al 2001a). In the past years, fluorometric methods, immunocapture enzyme assays and even high-throughput tandem mass spectrometry assays have been developed and optimised to allow (large-scale) screening for LSDs (Blanchard et al 2008;Dean et al 2006;Duffey et al 2010a;Duffey et al 2010b;Fuller et al 2011;Reuser et al 2011;Wang et al 2007;Wolfe et al 2011). However, all studies using DBS were feasibility studies, including only patients with a confirmed diagnosis of MPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of using DBS for enzymatic diagnosis of MPS and ML II/III has been demonstrated (Chamoles et al 2001b;Chamoles et al 2001a). In the past years, fluorometric methods, immunocapture enzyme assays and even high-throughput tandem mass spectrometry assays have been developed and optimised to allow (large-scale) screening for LSDs (Blanchard et al 2008;Dean et al 2006;Duffey et al 2010a;Duffey et al 2010b;Fuller et al 2011;Reuser et al 2011;Wang et al 2007;Wolfe et al 2011). However, all studies using DBS were feasibility studies, including only patients with a confirmed diagnosis of MPS.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several studies have shown the feasibility of the enzymatic diagnosis of MPS I, II or VI using DBS (Blanchard et al 2008;Chamoles et al 2001a;Chamoles et al 2001b;Dean et al 2006;Duffey et al 2010a;Duffey et al 2010b;Fuller et al 2011;Wang et al 2007;Wolfe et al 2011). However, none of these studies had a prospective design, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…NBS for five LSDs (Gaucher, Krabbe, Pompe, Fabry, and Niemann-Pick A/B) was described via the measurement of the respective enzyme activities in dried blood spots (DBS) from a single sample preparation with MS/MS (Blanchard et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Three separate preparations of each dilution were measured 5 times, and CV calculated as the standard deviation divided by mean × 100. It is estimated that each 3.3 mm dried blood spot disc corresponds to 3.6 μL of blood (Blanchard et al, 2008), and that concentrations of all the GAGs analyzed in this study were expressed as ng/mL of blood.…”
Section: Discussionmentioning
confidence: 99%